Live and Let Die: Rethinking Secondary Marginalization in the 21st Century. Issue 2 (3rd July 2019) - Spence, Lester K.
Abstract : Thirty years ago black populations were disproportionately HIV + and far more likely to die of AIDS than other populations. Yet and still black elected officials, civil rights organizations, and black institutions ignored the problem. Now, at least in major metropolitan areas, circumstances appear to have changed—not only do civil rights organizations, black elected officials, and a range of black institutions take HIV and AIDS seriously, it is not uncommon to find promotional materials urging black populations to get tested and to practice safe sex. What has changed since that moment? In this paper I argue that the increased visibility attending HIV/AIDS in black communities has come with increased responsibilizing of blacks with HIV/AIDS or at risk of contracting HIV.